2018
DOI: 10.1155/2018/7541904
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Right Subclavian Artery-Esophageal Fistulae

Abstract: An aberrant right subclavian artery (ARSA) is the most common aortic arch anomaly, but only 19 previous cases of ARSA-esophageal fistula have been reported. Six patients have survived their bleeding episode. We describe the case of a 44-year-old woman who developed massive hemoptysis. Laryngoscopy, bronchoscopy, head and neck angiogram, and median sternotomy did not reveal what was presumed initially to be a tracheoinnominate fistula. Contrasted CT showed an anomalous subclavian artery posterior to the esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Previously, aortic arch anomalies have been reported as a miscellaneous etiology of aortoesophageal fistulae [ 1 ]. A review of previously reported cases of aberrant subclavian artery-esophageal fistulae revealed the prolonged use of devices such as NG and endotracheal (ET) tubes as a major contributing factor [ 2 , 5 , 10 , 11 , 12 , 13 , 14 , 15 ]. NG and ET tubes are believed to create pressure necrosis and erosion on the area of the esophageal wall that is in contact with the tubes [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, aortic arch anomalies have been reported as a miscellaneous etiology of aortoesophageal fistulae [ 1 ]. A review of previously reported cases of aberrant subclavian artery-esophageal fistulae revealed the prolonged use of devices such as NG and endotracheal (ET) tubes as a major contributing factor [ 2 , 5 , 10 , 11 , 12 , 13 , 14 , 15 ]. NG and ET tubes are believed to create pressure necrosis and erosion on the area of the esophageal wall that is in contact with the tubes [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some cases were associated with esophageal cancer or recent procedures such as surgery and stent insertion, fistulae could be attributable to a prolonged use of NG and/or ET tubes in more cases. Therefore, some authors recommend screening intensive care patients and avoiding the long-term use of NG or ET tubes in patients with an aberrant subclavian artery [ 12 , 13 ]. Since conventional surgical repair takes considerable time, endovascular treatment such as temporary balloon occlusion or stent insertion is commonly performed for rapid bleeding control [ 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arterioenteric fistula is a rare complication of ARSA, most commonly associated with prolonged nasogastric (NGT) or endotracheal intubation (ETT), or presence of an oesophageal stent [2]. Diagnosis is difficult as patients present with rapid unexplained exsanguination with overwhelming haematemesis.…”
Section: Discussionmentioning
confidence: 99%
“…When these techniques are not possible, the final option is for thoracotomy or sternotomy to establish proximal arterial control via cross clamping of the aorta [6]. We describe the first case in the literature of an ARSA-esophageal fistula managed endovascularly without thoracotomy or sternotomy [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation